2016
DOI: 10.1016/j.ridd.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Do we really know what they were testing? Incomplete reporting of interventions in randomised trials of upper limb therapies in unilateral cerebral palsy

Abstract: Background: Incomplete reporting of components of interventions limits uptake of evidence into clinical practice. Aims:To evaluate the completeness of reporting of research and control interventions in randomised trials of upper limb therapies for children with unilateral cerebral palsy. Methods and procedures:Sixty randomized trials were included, encompassing 60 research and 68 control interventions. Using the 12-item Template for Intervention Description and Replication (TIDieR) checklist, two reviewers ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 72 publications
10
23
0
Order By: Relevance
“…The majority of these findings are consistent with previous evaluations of non‐pharmacological interventions using the TIDieR checklist, with all five previous studies reporting that intervention modifications (item 10) and fidelity (items 11 and 12) were most poorly reported . Reporting modifications to the planned intervention can enable readers to judge potential threats to internal and external validity, and may assist clinicians to avoid the same mistakes in practice .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The majority of these findings are consistent with previous evaluations of non‐pharmacological interventions using the TIDieR checklist, with all five previous studies reporting that intervention modifications (item 10) and fidelity (items 11 and 12) were most poorly reported . Reporting modifications to the planned intervention can enable readers to judge potential threats to internal and external validity, and may assist clinicians to avoid the same mistakes in practice .…”
Section: Discussionsupporting
confidence: 85%
“…The TIDieR checklist has the potential to reduce research waste by improving the ability to replicate interventions, enabling clinicians to implement effective interventions due to the availability of adequate information, and could streamline future research . Since its publication in 2014, the TIDieR checklist has been widely used to report on non‐pharmacological interventions at several stages of the research process , including by studies examining exercise‐based cardiac rehabilitation , physiotherapy interventions and upper limb therapies in unilateral cerebral palsy , and by two systematic reviews assessing telehealth‐delivered dietary intervention trials in chronic disease and trials of printed education material interventions, respectively . Two of the previous TIDieR studies found that none of the included studies completely reported all aspects of the interventions according to the TIDieR checklist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our limited sample, it seems that reporting of placebo components has improved slightly in the last decade. Our study also revealed that adequate reporting of placebo or sham control interventions is poorer than adequate reporting of active interventions …”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed that adequate reporting of placebo or sham control interventions is poorer than adequate reporting of active interventions. 22,23…”
Section: Comparison With Other Related Studiesmentioning
confidence: 99%